Complete Reversible Refolding of a G-Protein Coupled Receptor on a Solid Support. - Natalie Di Bartolo; Emma L R Compton; Tony Warne; Patricia C Edwards; Christopher G Tate; Gebhard F X Schertler; Paula J Booth (PLoS ONE, 2016)
The factors defining the correct folding and stability of integral membrane proteins are poorly understood. Folding of only a few select membrane proteins has been scrutinised, leaving considerable deficiencies in knowledge for large protein families, such as G protein coupled receptors (GPCRs). Complete reversible folding, which is problematic for any membrane protein, has eluded this dominant receptor family. Moreover, attempts to recover receptors from denatured states are inefficient, yielding at best 40-70% functional protein. We present a method for the reversible unfolding of an archetypal family member, the β1-adrenergic receptor, and attain 100% recovery of the folded, functional state, in terms of ligand binding, compared to receptor which has not been subject to any unfolding and retains its original, folded structure. We exploit refolding on a solid support, which could avoid unwanted interactions and aggregation that occur in bulk solution. We determine the changes in structure and function upon unfolding and refolding. Additionally, we employ a method that is relatively new to membrane protein folding; pulse proteolysis. Complete refolding of β1-adrenergic receptor occurs in n-decyl-β-D-maltoside (DM) micelles from a urea-denatured state, as shown by regain of its original helical structure, ligand binding and protein fluorescence. The successful refolding strategy on a solid support offers a defined method for the controlled refolding and recovery of functional GPCRs and other membrane proteins that suffer from instability and irreversible denaturation once isolated from their native membranes.